Sociology in Theology - Flanagan, K. author. aut Link
X, 189 p.
Keywords: This is an original study of the sociological imagination in regard to visual culture. It explores the reflexive dimensions of choice over seeing or not seeing in relation to paintings, images and islands. Bourdieu, Goffman and Simmel provide the basis for insights into how reflexivity in sociology has unexplored theological implications.